Ythdf2 regulates cardiac remodeling through its mRNA target transcripts - Kmietczyk, Vivien; Oelschläger, J.; Gupta, Parul; Varma, Eshita; Hartl, S.; Furkel, Jennifer; Konstandin, Mathias; Marx, A.; Loewenthal, Z.; Kamuf-Schenk, V.; Jürgensen, L.; Stroh, C.; et al. (Journal of molecular and cellular cardiology, 2023)
m6A mRNA methylation controls cardiomyocyte function and increased overall m6A levels are a stereotyping finding in heart failure independent of the underlying etiology. However, it is largely unknown how the information is read by m6A reader proteins in heart failure. Here we show that the m6A reader protein Ythdf2 controls cardiac function and identified a novel mechanism how reader proteins control gene expression and cardiac function. Deletion of Ythdf2 in cardiomyocytes in vivo leads to mild cardiac hypertrophy, reduced heart function, and increased fibrosis during pressure overload as well as during aging. Similarly, in vitro the knockdown of Ythdf2 results in cardiomyocyte growth and remodeling. Mechanistically, we identified the eucaryotic elongation factor 2 as post-transcriptionally regulated by Ythdf2 using cell type specific Ribo-seq data. Our study expands our understanding on the regulatory functions of m6A methylation in cardiomyocytes and how cardiac function is controlled by the m6A reader protein Ythdf2.